Consultation on proposed amendments to the Local Authorities (Capital Finance and Accounting) (England) Regulations 2003 in relation to the use of capital receipts : Summary of Responses and Government Response.: Summary of Responses and Government Response. (February 2015) - Great Britain., Department for Communities; Local Government,
No abstract available